Evaluating Retail micro-SME Resilience: Failing, Surviving and Thriving as Outcomes of Bricolage - Dafydd Cotterell (Institute of Small Business and Entrepreneurship (ISBE) Conference, 2024)
The global business environment faces an enduring threat from numerous ongoing unprecedented crises. These crises – such as Mpox, Brexit, climate change, growing political tensions, and war in Europe and the Middle East – have created complex challenges for business, where the development of resilience is key. In a bid to further understand resilience, many researchers are exploring novel theories such as resource bricolage theory. In this study, we evaluate the enablers for successful bricolage deployment within retail micro-SMEs during the unprecedented crisis, Covid-19. Using a qualitative research method, we find that business experience, business age, and business support all enable retail micro-SMEs to successfully deploy bricolage by means of resilience. Our findings hold significant theoretical and practical implications for both academics and practitioners interested in resource bricolage. Namely, our study extends knowledge on the enablers of bricolage, providing the critical link between the theoretical and practical implementation of bricolage. If bricolage research is to be impactful and relevant to practice, then research must identify how bricolage can be deployed and not only identify its applications. This research study contributes to this call.